Literary genres and storytelling fun in the novel (The Bodies and their Shades) - Behnam Barada, Haitham (Journal of College of Education, 2020)
This study seeks to read the novel (The Bodies and its Misguidance) by Haitham Bahnam Barada to highlight its openness to more than one literary and artistic type, so that the uterus embraces these types and it transcends the traditional view of the novel to respond to the writer’s desire to shape a new world through a formal mixing influencing The content gives the recipient the opportunity to find multiple types, in a text characterized by contrast and aesthetic excitement, shaved by its creative writer to be a symbol and a unique experience. The study adopted a descriptive approach with an analytical view, and its aim is to reveal the intertwining of literary and artistic types in the text of the novel, which distinguishes the contemporary novel, which is subject to openness, and acceptance of the characteristics of the other type.